2018
DOI: 10.1002/lsm.22782
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of collagen and elastic fibers after intense pulsed light treatment of mouse skin

Abstract: IPL treatment significantly increased the number of collagen and elastic fibers within the dermis and improved the parallel distribution of collagen fibers in relation to the epidermis. These results were evident after three IPL treatments. Lasers Surg. Med. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Paraffin-embedded sections were examined using hematoxylin and eosin (H&E), Masson’s trichrome and picrosirius red staining as previously described 51,54,55 . The severity of collagen deposition and lung fibrosis was assessed by measuring the Masson’s trichrome and picrosirius red staining, respectively 56,57 .…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin-embedded sections were examined using hematoxylin and eosin (H&E), Masson’s trichrome and picrosirius red staining as previously described 51,54,55 . The severity of collagen deposition and lung fibrosis was assessed by measuring the Masson’s trichrome and picrosirius red staining, respectively 56,57 .…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Pathology specimens obtained after IPL treatment show enhanced collagen and elastic fibre formation in the papillary and sub-papillary dermis, resulting in an increase in volume which in turn leads to smoothing the upper dermal layers and the increased epidermal turnover. 15,16 In an in vitro study, Wong et al 17 showed that after IPL irradiation, the number of live fibroblasts increases more than 100%. They postulated that the IPL rejuvenation effect is concurrent with an increase in extracellular matrix volume resulting from the enhanced expression of collagen III and TGF-B1 genes.…”
Section: Discussionmentioning
confidence: 99%
“…The photothermal effects lead to reversible thermal damage to surrounding collagen and induction contraction of collagen fibers and fiber remodeling. 50 Clinical studies on the effectiveness on skin tightening have shown incongruent results. Multiple studies have noted improvement in skin elasticity as well as increased deposits of collagen in treated areas.…”
Section: Ipl Therapymentioning
confidence: 99%